Matematika/Išvestinė: Skirtumas tarp puslapio versijų

:<math>\left( \frac{1}{v} \right)'=-\frac{v'}{v^2} .</math>
:Tam tikslui rasime funkcijos <math> \frac{1}{v} </math> pokytį:
:<math>\Delta\left( \frac{1}{v} \right)=\frac{1}{v(x_0+\Delta x)}-\frac{1}{v(x_0)} =\frac{v(x_0)-v(x_0+\Delta x)}{v(x_0)v(x_0+\Delta x)}=\frac{-\Delta v}{v(x_0)(v(x_0)+\Delta xv)}.</math>
:Iš čia
:<math>\frac{\Delta\left( \frac{1}{v} \right)}{\Delta x}=\frac{-\frac{\Delta v}{\Delta x}}{v(x_0) (v(x_0)+\Delta xv)}.</math>
:Jei <math>\Delta x\to 0,</math> tai <math>\frac{\Delta v}{\Delta x}\to v'</math> (kadangi ''v'' diferencijuojama taške <math>x_0</math>), <math>\Delta v \to 0.</math> Todėl
:<math>\frac{\Delta\left( \frac{1}{v} \right)}{\Delta x}=\frac{-v'}{v\cdot v}=-\frac{v'}{v^2}, \;</math> t. y. <math>\; \left( \frac{1}{v} \right)'=-\frac{v'}{v^2} ;</math>
1 740

pakeitimų